Evaluación de tres índices de cosecha y desinfección en dos híbridos de pimiento (Capsicum annuum. híbrido cortes y coach) en el campus experimental Salache 2019 – 2020. - Tomaico Tipan, Sandra Maribel (2020)
The study was done at Salache Academic Experimental Center of the Technical University of Cotopaxi, during the period 2019-2020. The objective was to evaluate the harvest indexes and the postharvest behavior of two pepper hybrids (Cortes and Coach) in disinfection with sodium hypochlorite at two volumes (0.3% and 0.5%) and a control without disinfection. The work has two phases, the first one was carried out in the field, in which the hybrids were harvested at different color index at 193 days after planting and the second phase was carried out in the agronomy laboratory, it was considered a product 50 mm in diameter for each index and hybrid for taking indicators to evaluate stories such as: weight, firmness, soluble solid, pH, humidity, ashes, pathophysiology and diseases. An experimental DBCA design with factorial arrangement A*B*C with 3 repetitions and a total of 54 experimental units was established. The best harvest index was the green index, registering the best results during the 11 days of the trial. It maintained a weight of 334.53 g on the last day, a weight variation of 4.78%, a firmness of 1.72 kg, a soluble solid of 6.7 ° Brix, a pH of 4.47, a humidity of 96.62%, ash content of 1.12% and an incidence of pathophysiology and diseases of 11.11% loss. The best hybrid was the Cortes with a weight of 338.22 g, a weight variation of 1.72%, a firmness of 0.79 kg, a soluble solid of 8.58 ° Brix, a pH of 4.38 and an incidence of physiopathies and diseases of 32.59%. The best disinfection was the second concentration with 0.5% sodium hypochlorite with a total of 21.11% incidence of phytopathies and diseases registered until the last day of the investigation. The best treatment of the interaction of the three factors was the A1B2C3 (green index, hybrid cuts, 0.5% hypochlorite) excelling with a final weight of 389.54 g and a firmness of 2.93 kg, emphasizing that the highest content The soluble solid is found in the A3B2C3 treatment (red index, hybrid cuts, 0.5% hypochlorite) with a value of 11 ° Brix.